Contextual Teaching and Learning Method Media Props for Building Projection Images - Ariani Rintowati; Tri Rijanto (Universitas Ahmad Dahlan, 2023)
The time of teaching the construction of utility building educators had difficulty. Most of the students have difficulty in translating three-dimensional (3D) images into two-dimensional (2D) images. Learning media is needed to deal with these difficulties. Learning media that can encourage and guide students' thinking skills. The purpose of this study is to determine students' understanding in translating three-dimensional images into two-dimensional images. The method used is classroom action research. ) with two stages or cycles. The first cycle knows the initial concept of students' difficulties, while the second cycle of learning uses three-dimensional cube media and tests to determine students' understanding. This study was applied to class XI DPIB3 SMK N 1 Mojokerto with 32 students. Data were analyzed using the Rasch Model. The results of the study using the contextual method of 3D cube props obtained quite good results, improving a good teaching process can improve understanding of drawing two-dimensional projections. The principle of this projection image is used for bestek drawings, working drawings and other drawings on building works. Drawings at the planning and implementation stages in building projects.